Collaborative Governance in HIV/AIDS Prevention in Tanjungpinang City in 2024 - Rintaria Rintaria; Yudhanto Satyagraha Adiputra; Uly Sophia (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines multi-actor administrative arrangements in epidemic prevention within municipal governance frameworks. Qualitative descriptive methodology was utilized through semi-structured interviews and documentary analysis involving state agencies and civil society organizations. The analytical framework established by Ansell and Gash evaluates starting conditions, facilitative leadership, and institutional design. Findings indicate that bridging resource gaps and establishing formal regulatory protocols are essential for effective cross-sectoral coordination. Furthermore, transparent accountability mechanisms and adaptive institutional structures significantly enhance service delivery for vulnerable populations. The research highlights that sustained collaboration requires balancing bureaucratic authority with community-level engagement to achieve enduring public health outcome.